2015
DOI: 10.5194/soil-1-35-2015
|View full text |Cite
|
Sign up to set email alerts
|

The past, present, and future of soils and human health studies

Abstract: Abstract. The idea that human health is tied to the soil is not a new one. As far back as circa 1400 BC the Bible depicts Moses as understanding that fertile soil was essential to the well-being of his people. In 400 BC the Greek philosopher Hippocrates provided a list of things that should be considered in a proper medical evaluation, including the properties of the local ground. By the late 1700s and early 1800s, American farmers had recognized that soil properties had some connection to human health. In the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(91 citation statements)
references
References 155 publications
0
85
0
6
Order By: Relevance
“…Soils are an important source of services (filtration of water, exchange of gases with the atmosphere, foundation material for construction) and resources (food, fiber, fuel, clay for construction, medications) for humans (Mol and Keesstra, 2012;Brevik and Sauer, 2015). Soils play a pivotal role in the Earth system to manage the hydrological, erosional, geochemical, and biological cycles (Smith et al, 2015;Willaarts et al, 2016) which makes sustainable soil management and conservation necessary to achieve a sustainable world (Keesstra et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Soils are an important source of services (filtration of water, exchange of gases with the atmosphere, foundation material for construction) and resources (food, fiber, fuel, clay for construction, medications) for humans (Mol and Keesstra, 2012;Brevik and Sauer, 2015). Soils play a pivotal role in the Earth system to manage the hydrological, erosional, geochemical, and biological cycles (Smith et al, 2015;Willaarts et al, 2016) which makes sustainable soil management and conservation necessary to achieve a sustainable world (Keesstra et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The people originating from the states of NE India are phenotypically different from other Indians. Moreover, people with an ancestral background/history associated with these states also possess the similar morphology [2]. We hypothesize that the facial features of the most of the human population with the NE Indian foundation or ancestral background are influenced by the soil constituency of that geographical area.…”
Section: Hypothesismentioning
confidence: 99%
“…Besides, its role in the plants growth, soil impacts the life, including humans, to a greater extent. It acts as an indirect source of nutrition for humans as it ensures the supply of nutrients to humans through the plants and their products consumed by them [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, numerous studies have indicated that restoration needs to recover soil functionality, and this call is taking place all over the world (Ahmad et al, 2013;Johnston et al, 2013;Mao et al, 2014;Moreno et al, 2014;Novara et al, 2014;Roy and McDonald, 2015;Sacristán et al, 2015;Sadeghi et al, 2015;Srivastava et al, 2014). Some authors indicate that this task should be accomplished with a broad view by considering how soils can interfere with human health (Brevik and Sauer, 2015).…”
Section: N Seco-reigosa Et Al: Adsorption Desorption and Fractionamentioning
confidence: 99%